2014
DOI: 10.3389/fpsyg.2014.00679
|View full text |Cite
|
Sign up to set email alerts
|

The Einstellung effect in anagram problem solving: evidence from eye movements

Abstract: The Einstellung effect is the counterintuitive finding that prior experience or domain-specific knowledge can under some circumstances interfere with problem solving performance. This effect has been demonstrated in several domains of expertise including medicine and chess. In the present study we explored this effect in the context of a simplified anagram problem solving task. Participants solved anagram problems while their eye movements were monitored. Each problem consisted of six letters: a central three-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 39 publications
1
30
0
2
Order By: Relevance
“…Additionally, a negative but not significant association was found between the number of set problems solved and the number of critical problems solved using simple strategies (M = 1.47, SD = 1.32, r(79) = −.22, p = .050). This finding suggests that individuals who were more likely to establish mental set in the first half of the task were less likely to break mental set in the second half of the task, consistent with previous studies in which mental set resulted from prior experience or domain-specific knowledge (e.g., Bilalić et al, 2010;Crooks & McNeil, 2009;Ellis & Reingold, 2014;Wiley, 1998). Table 3).…”
Section: Set Problemssupporting
confidence: 88%
“…Additionally, a negative but not significant association was found between the number of set problems solved and the number of critical problems solved using simple strategies (M = 1.47, SD = 1.32, r(79) = −.22, p = .050). This finding suggests that individuals who were more likely to establish mental set in the first half of the task were less likely to break mental set in the second half of the task, consistent with previous studies in which mental set resulted from prior experience or domain-specific knowledge (e.g., Bilalić et al, 2010;Crooks & McNeil, 2009;Ellis & Reingold, 2014;Wiley, 1998). Table 3).…”
Section: Set Problemssupporting
confidence: 88%
“…Luchins' striking demonstration that experience can induce inflexibility of thought has been successfully repeated using a variety of tasks, including those involving mathematical problems [24], verbal reasoning [25] and more visual tasks [26]. In addition, mental set has been shown both to affect people facing problems that are new to them [27,28,29] and also experts tackling problems that are within their field of expertise [13,30,31,32].…”
Section: Mental Set Paradigmsmentioning
confidence: 99%
“…In addition, Godau et al ( 2014 ) found that experts in arithmetic problem solving spontaneously used arithmetic shortcuts. Finally, Ellis and Reingold ( 2014 ) examined the Einstellung effect (i.e., where the first idea that comes to mind blocks finding the best solution to a problem) using this methodology and noted its relevance to understanding expert flexibility (see Bilalić and McLeod, 2014 ).…”
Section: Cognitive Processes In Expertisementioning
confidence: 99%